2020
DOI: 10.3390/jcm9010281
|View full text |Cite
|
Sign up to set email alerts
|

Serum Exosomal MicroRNA, miR-10b-5p, as a Potential Diagnostic Biomarker for Early-Stage Hepatocellular Carcinoma

Abstract: Exosomal microRNAs (exo-miRs) have been promising cancer biomarkers. MiRs in hepatocellular carcinoma (HCC) cell-derived exosomes (HEX) were analyzed to identify reliable serum biomarkers for HCC. To detect overexpressed miRs in HEX, extracted exosomal small RNAs from human HCC cell lines and normal hepatocytes were sequenced and analyzed. Clinical significance of the overexpressed miRs in HEX was evaluated using quantitative real-time PCR (qRT-PCR) on serum samples of a validation cohort consisting of 28 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 27 publications
1
65
0
Order By: Relevance
“…Mir‐10b is a tumor‐associated miRNA in many types of cancer. It could be enriched in exosomes of hepatocellular carcinoma cells and was a potential marker for the diagnosis of early‐stage hepatocellular carcinoma 14 . Hypoxia could induce the expression of miR‐10b‐3p and promote the growth and metastasis of esophageal squamous cell carcinoma by targeting TSGA10 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Mir‐10b is a tumor‐associated miRNA in many types of cancer. It could be enriched in exosomes of hepatocellular carcinoma cells and was a potential marker for the diagnosis of early‐stage hepatocellular carcinoma 14 . Hypoxia could induce the expression of miR‐10b‐3p and promote the growth and metastasis of esophageal squamous cell carcinoma by targeting TSGA10 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Following this study, many other investigations identified several miRNAs in exosomes as diagnostic (Table 2) or prognostic (Table 3) biomarkers in HCC. [132] miR-744 ↓ 68 HCC and 52 normal liver tissue samples Proliferation and chemoresistance [114] CHB: chronic hepatitis B; CLD: chronic liver disease; HCC: hepatocellular carcinoma; LC: liver cirrhosis.…”
Section: Exosomal Mirnas As Potential Biomarkers In Hccmentioning
confidence: 99%
“…High protein and RNA expression was observed on the surface of EVs in the majority of studies involving HCC cases. The most thoroughly investigated marker was miRNAs associated with small EVs [ 82 , 83 , 84 , 85 ]. Data on the ability of miRNAs to distinguish HCC from healthy individuals showed that exosomal miR-122, miR-148a, miR-1246 [ 82 ], miR-10b-5p, miR-18a-5p, miR-215-5p and miR-940 [ 83 ] may be used in clinical practice.…”
Section: Evs In Gastrointestinal (Gi) and Liver Cancer Managementmentioning
confidence: 99%
“…Two points need to be stressed here. First, the high degrees of sensitivity and specificity of these miRNAs, especially miR-122 [ 82 ] and miR-10b-5p [ 83 ], for HCC diagnosis were confirmed. Second, the measurement of exosomal miR-215-5p in blood might give additional information on patients’ prognosis [ 83 ].…”
Section: Evs In Gastrointestinal (Gi) and Liver Cancer Managementmentioning
confidence: 99%